Transient heat and mass transfer of hydromagnetic effects on the flow past a porous medium with movable vertical permeablesheet - Salawu, Sulyman Olakunle; Okedoye, Akindele Michael (Zielona Góra: Uniwersytet Zielonogórski)
An unsteady flow of heat and species transport through a porous medium in an infinite movable vertical permeable flat surface is considered. The hydromagnetic chemical reactive fluid flow is stimulated by the thermal and solutant convection, and propelled by the movement of the surface. The formulated nonlinear flow equations in time space are solved analytically by asymptotic expansions to obtain solutions for the flow momentum, energy and chemical concentration for various thermo-physical parameters.
Keywords: movable plate; porosity; suction; perturbation method; MHD flow